2017
DOI: 10.1111/joor.12473
|View full text |Cite
|
Sign up to set email alerts
|

Single mandibular implant study – denture satisfaction in the elderly

Abstract: To investigate whether there are differences in patients' denture satisfaction when an implant placed in the midline of the edentulous mandible is loaded either immediately or three months later, after second-stage surgery. One hundred and fifty-eight edentulous patients received a single implant in the midline of the mandible. After randomisation, it was loaded either immediately after implant placement (N = 81, group A) or three months later, after a submerged healing phase and a second-stage surgery (N = 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…For implant‐retained overdentures in the edentulous jaw, the current literature shows that one to two implants in the mandible and four implants in the maxilla are considered sufficient to provide patients with improved comfort . These numbers of implants are in accordance with a review and meta‐analysis evaluating the survival rate of implants in the edentulous jaw .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For implant‐retained overdentures in the edentulous jaw, the current literature shows that one to two implants in the mandible and four implants in the maxilla are considered sufficient to provide patients with improved comfort . These numbers of implants are in accordance with a review and meta‐analysis evaluating the survival rate of implants in the edentulous jaw .…”
Section: Discussionmentioning
confidence: 66%
“…28 For implant-retained overdentures in the edentulous jaw, the current literature shows that one to two implants in the mandible and four implants in the maxilla are considered sufficient to provide patients with improved comfort. [34][35][36][37] These numbers of implants are in accordance with a review and meta-analysis evaluating the survival rate of implants in the edentulous jaw. 38 However, in the present study, implants were planned and placed in strategic positions to support existing tooth-supported telescopic crowns and to reduce the load on the teeth during function.…”
Section: Discussionmentioning
confidence: 88%
“…Immediate loading was carried out in five studies, while at six weeks postoperatively, early loading was carried out in three studies . All the other studies undertook a conventional (delayed) loading protocol, that ranged between 2 and 4 months .…”
Section: Resultsmentioning
confidence: 99%
“…Two implant failures were reported in the bone healing phase of the conventionally loaded implants . Passia et al reported 9 failed immediately loaded implants, and one failed conventionally loaded implant . Liddelow et al observed a 100% survival rate in immediately loaded oxidized implants while all the immediately loaded machined implants had failed…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation